PEMBERLAKUAN HUKUMAN PIDANA MATI DI DALAM NEGARA PANCASILA - Aturkian Laia (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2023)
The implementation of the death penalty law is a very interesting and endless discussion between those who agree and those who disagree, and provide each other with arguments from various aspects and most importantly where the implementation of the death penalty has been regulated in the Constitution and those who disagree put forward the Constitution. that the prohibition on the imposition of the death penalty, the pros and cons both maintain arguments and the application of the death penalty not only among legal practitioners but has been consumed by the public and clergy in the discussion of the imposition of the death penalty. This journal has a problem formulation, namely first, how are the Death Penalty Rules in Positive Law in Indonesia? Second, what are the considerations for the implementation of the death penalty from the perspective of Pancasila? This research uses normative research methods.